Equivalent Modeling of Temperature Field for Amorphous Alloy 3D Wound Core Transformer for New Energy - Han, Jianwei; Hou, Xiaolin; Yao, Xinglong; Yan, Yunfei; Dai, Zonghan; Wang, Xiaohui; Zhao, Peng; Zhuang, Pengzhe; Yu, Zhanyang (Energies (Basel), 2025)
It is of the utmost importance to accurately solve the transformer temperature field, as it governs the overall performance and operational stability of the transformer. However, the intricate structure of high- and low-voltage windings, insulating materials, and other components presents numerous challenges for modeling. Temperature exerts a significant influence on insulation aging, and elevated temperatures can notably accelerate the degradation process of insulation materials, reducing their service life and increasing the risk of electrical failures. In view of this, this paper proposes an equivalent modeling method of the temperature field of the transformer HLV winding and studies the refined modeling of the winding part. First of all, in order to reduce the difficulty of temperature field modeling, based on the principle of constant thermal resistance, the fine high- and low-voltage windings are equivalent to large conductors, and the equivalent thermal conductivity coefficient of the high- and low-voltage windings is obtained, which improves the calculation accuracy and shortens the calculation time. Secondly, we verify the feasibility of the equivalent model before and after the simulation, analyze the influence of different boundary conditions on the winding temperature field distribution, and predict the local hotspot location and temperature trend. Finally, a 50 kVA amorphous alloy winding-core transformer is tested on different prototypes to verify the effectiveness of the proposed method.